Study of Light Pollution Characteristics in Berau with Sky ‎Quality Meter - Bayyinah, Rahmatul; Pramudya, Yudhiakto (Diponegoro University Semarang Indonesia, 2024)
The quality of night sky conditions can affect the results of astronomical ‎observations and ‎the ‎survival of wildlife, one of which is sea turtles. One of the causes of the ‎declining quality of ‎the night ‎sky is light pollution. To identify a location's light pollution ‎levels and the quality ‎of the night sky, it ‎is possible to measure the night sky brightness with ‎the Sky Quality ‎Meter (SQM). This ‎research specifically focuses on assessing night sky conditions in Berau, an important sea turtle conservation area, through analysis of SQM. By conducting observation through the period May-July 2022, covering each of the different moon phase, the objectives of this research to quantify the brightness of the night sky in Berau, measured in magnitude per arc square (‎mag/arcsec2) to describe the characteristics of light pollution in Berau and interpreted on the Naked Eye Limiting Magnitude (NELM) scale and the Bortle scale. Based ‎on the research results, ‎the highest frequency probability distribution was ‎observed from the ‎value of the sky brightness ‎level measured using SQM in Berau, with the ‎highest value ‎obtained at the new moon phase, 19.60 ‎mag/arcsec2, the conversion value in ‎NELM being ‎‎4.68, and in the Bortle scale, grade 7 with the ‎suburban transition category. ‎And for the ‎lowest value obtained at the time of the full moon ‎phase, 16.66 mag/arcsec2 with ‎a ‎conversion value in NELM of 2.26, and on the Bortle scale, it is in ‎class 9 with the ‎category ‎of the inner-city sky.‎